Correlation Between Knowledge of Health Information About Picky Eating, Supplementary Feeding, Management Ability of Appetite Herbs - Muflih, Muflih; Widaryanti, Rahayu; Indrawati, Fika Lilik; Trisagita, Natasya Gabryella (Peneliti Teknologi Teknik Indonesia, 2023)
Picky eaters continue to pose challenges in providing additional food, hindering efforts to address child stunting. Thus, understanding the causes of picky eating in relation to maternal knowledge of health information about picky eaters, supplementary feeding management, and appetite herbs is crucial. This study aims to explore the correlation between knowledge of health information about picky eater, supplementary feeding, and the ability to manage food and herbal appetite in mothers of stunted children in Srimartani Village, Piyungan, Yogyakarta. Employing a cross-sectional survey design, the study involved 27 mothers (aged 23-42) of stunted children in October 2022. A research instrument comprising 21 questions was developed based on the concept of picky eating, adapted to the research context. Data analysis employed Kendall's tau_b statistical test to assess correlations. Stunting data were obtained from documented diagnoses at the local community health center, including malnourished toddlers and undernourished children. Findings revealed no correlation between knowledge of health information about picky eater and supplementary feeding, as well as between supplementary feeding and the ability to manage supplementary feeding and appetite herbs. However, a significant correlation was observed knowledge of health information about between picky eater and the ability to manage additional food and appetite herbs. In conclusion, higher picky eater knowledge was associated with better ability to manage additional food and appetite herbs, while knowledge of supplementary feeding did not show such a correlation. Further research with a more representative sample is recommended to provide a comprehensive understanding of the picky eater phenomenon